Symbiotic Interaction: 5th International Workshop, Symbiotic 2016, Padua, Italy, September 29-30, 2016, Revised Selected Papers - Gamberini, Luciano; Spagnolli, Anna; Jacucci, Giulio; Blankertz, Benjamin; Freeman, Jonathan (Information Systems and Applications, incl. Internet/Web, and HCI, 2017)
human-computer interaction; machine learning; cyber-physical systems